Combining variant detection and fragment length analysis improves detection of minimal residual disease in postsurgery circulating tumour DNA of stage II–IIIA NSCLC patients. Issue 14 (27th June 2022) - Vessies, Daan C. L.; Schuurbiers, Milou M. F.; van der Noort, Vincent; Schouten, Irene; Linders, Theodora C.; Lanfermeijer, Mirthe; Ramkisoensing, Kalpana L.; Hartemink, Koen J.; Monkhorst, Kim; van den Heuvel, Michel M.; van den Broek, Daan
Abstract : Stage II–IIIA nonsmall cell lung cancer (NSCLC) patients receive adjuvant chemotherapy after surgery as standard‐of‐care treatment, even though only approximately 5.8% of patients will benefit. Identifying patients with minimal residual disease (MRD) after surgery using tissue‐informed testing of postoperative plasma circulating cell‐free tumour DNA (ctDNA) may allow adjuvant therapy to be withheld from patients without MRD. However, the detection of MRD in the postoperative setting is challenging, and more sensitive methods are urgently needed. We developed a method that combines variant calling and a novel ctDNA fragment length analysis using hybrid capture sequencing data. Among 36 stage II–IIIA NSCLC patients, this method distinguished patients with and without recurrence of disease in a 20 times repeated 10‐fold cross validation with 75% accuracy ( P  = 0.0029). In contrast, using only variant calling or only fragment length analysis, no signification distinction between patients was shown ( P  = 0.24 and P  = 0.074 respectively). In addition, a variant‐level fragmentation score was developed that was able to classify variants detected in plasma cfDNA into tumour‐derived or white‐blood‐cell‐derived variants with 84% accuracy. The findings in this study may help drive the integration of various types of information from the same data, eventually leading to cheaper and more sensitive techniques to be used in this challenging clinical setting. Abstract : Blood and tissue from 36 stage II–III NSCLC patients and 15 risk‐ and age‐matched patients with nonmalignant disease were analysed with targeted hybrid capture sequencing to detect postsurgery minimal residual disease (MRD) in the blood, prior to adjuvant therapy. Our combined variant calling and fragmentomics MRD model was capable of stratifying patients with and without recurrence with 75% accuracy ( P  = 0.0029).